PENYELESAIAN SENGKETA DALAM PERJANJIAN WARALABA - Berliana, Marsela; Urbanisasi, Urbanisasi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Franchising is an agreement between two parties, in which one party is given intellectual property rights to use and use that right or an invention or commercial property belonging to another party with a reward based on the terms and sale of goods or services. This type of research in the preparation of legal research uses normative research. As for the results of this study, the franchise agreement itself has factors that can cause disputes between the two parties, namely the Frenchisor and the Frenchisee. And also legal remedies that can be taken by both parties can be resolved through litigation and non-litigation.